Contribution to the Glolarnaca Gorochov, 2008 (Orthoptera: Gryllacrididae: Hyperbaeninae) from China - Yang, Zizhon; Lu, Xiangyi; Bian, Xun (Zootaxa, 2021)
Herein two new species of Glolarnaca Gorochov, 2008 are reported. Images illustrating the morphology of the two new species are provided. And the type specimens are deposited in the Institute of Entomoceutics Research, Dali University (DUIER) and Guangxi Normal University (GXNU).